2019
DOI: 10.1017/s0144686x19000667
|View full text |Cite
|
Sign up to set email alerts
|

After the care journey: exploring the experiences of family carers of people living with dementia

Abstract: While the burden of caring for people living with dementia has been well documented, considerably less is known about how carers transition into post-care life. This study aimed to understand the experiences of primary family care-givers of people with dementia after the person with dementia has died. A specific focus of the research was understanding the barriers to transitioning into a positive post-care life, and facilitators that help sustain carers as they move forward after their care journey has ended. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…On the other hand, the loss of autonomy, the degree of cognitive deterioration of the patient with dementia, their physical manifestations and, especially, their behavioural manifestations, also influence burden [19][20][21]. However, some authors such as Van der Lee et al [22] place manifestations or behavioural disorders as the aspect of dementia that has the greatest impact on caregiver burden.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the loss of autonomy, the degree of cognitive deterioration of the patient with dementia, their physical manifestations and, especially, their behavioural manifestations, also influence burden [19][20][21]. However, some authors such as Van der Lee et al [22] place manifestations or behavioural disorders as the aspect of dementia that has the greatest impact on caregiver burden.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover due to the short follow-up period of studies in this area, it is often difficult to extrapolate what the immediate and long-term effects of discontinuing care provision has had on the former carer. Jameson et al (2019) conducted a qualitative study in Australia of discontinued carers, who provided care to people living with dementia. The authors found that after the person with dementia died, spousal carers tended to struggle with the transition out of the caring role more so than adult children who had provided care for a parent with dementia.…”
Section: Associations Of Discontinuing Care the Caring Rolementioning
confidence: 99%